Tangible and intangible costs of "protecting human subjects": The impact of the National Research Act of 1974 onuniversity research activities - Jacobs, Frederic; Zonnenberg, Arina (Education Policy Analysis Archives, 2004)
This article (1) examines the overall structure of regulatory research oversight in the United States; (2) details the origins and evolution of federal legislation pertaining to the protection of human subjects in biomedical and behavioral treatment and research; and (3) describes the expansion of oversight regulation from biomedical and behavioral treatment areas to the social sciences. In addition, the paper describes three areas identified by compliance administrators as susceptible to abuse: (1) informed consent, (2) assessment of risks and benefits, and (3) equitable selection of human subjects. There is a discussion of existing tensions in the implementation of oversight policies and procedures. Finally, the paper identifies four issues for future consideration: (1) scope of the mandate regarding protection of human subjects, (2) impact on the nature of research being undertaken, (3) financial burden of compliance and oversight activities, and (4) ethical standards, constraints, and potential.